PERANAN E-SAMSAT DALAM MENINGKATKAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SAMSAT SOREANG KAB.BANDUNG - HASNA NURSABRINA (JEBS (Journal of Economic and Business Student), 2023)
This study aims to determine the role of E-Samsat in increasing motor vehicle tax revenues in Samsat Soreang Kab. Bandung, as well as to find out the problems and efforts made related to the motor vehicle tax payment service system through E-Samsat. The method used in this study is a descriptive qualitative method and the source of the data used is secondary data in the form of the level of PKB Principal Revenue Realization (PerType of Motorized Vehicles) in Samsat Soreang Kab. Bandung. Based on the results of the research obtained, it states that E-Samsat plays a role in taxpayers, because it can be seen in the level of realization of motor vehicle tax revenues which has increased from 2018-2021. There are obstacles in the role of E-Samsat, namely servers that are less supportive and not fully online system. To overcome these obstacles, Samsat Soreang has made an effort to open a public mall payment outlet, namely payments that can be made offline. The advice given by the author in the study is to improve E-Samsat into a full online system, especially in the procedure for paying motor vehicle taxes, because with this This payment process will be more optimal.